Implications of Urbanization and Climate Change for Oregon White Oak (Quercus garryana) Regeneration, Planning, and Management in the Pacific Northwest - Michalak, Julia (My University, 2014)
Land-cover and climate change pose significant challenges to ecological planning and management. Ecological responses to these changes are mediated by the interactions between landscape structure, biodiversity, and ecosystem function. I use a case study of Oregon white oak in the rapidly urbanizing coastal Pacific Northwest to explore these interactions and their implications for planning. Biodiversity changes dramatically as urban development intensifies. Yet the subsequent impacts on ecological functions remain relatively unexplored. I hypothesize that urbanization alters the community composition of acorn-dispersing animal species, and that this, in conjunction with fine-scaled habitat and foraging interactions, will generate unique dispersal and regeneration patterns in urban oak woodlands. I tracked the dispersal of individual acorns directly to test whether dispersal differs in urban and non-urban landscapes and used experimental acorn plantings and observations of seedling and sapling abundance to test whether urbanization influences later stages of oak regeneration. I found that more acorns were consumed and dispersal distances were shorter in urban oak woodlands making acorn dispersal services inferior to those in non-urban landscapes. Seedling production and abundance did not differ between urban and non-urban sites, although young saplings were less abundant in urban oak woodlands. Understanding the effects of landscape patterns on regeneration processes is essential for learning how to manage urban oak ecosystems. Due to their complexity, understanding how ecological systems will respond to climate change is highly uncertain. I evaluate potential climate impacts on Oregon white oak in the Willamette Valley using a range of information sources to identify consensus, uncertainty, and knowledge gaps in our understanding of oak vulnerability. Based on this assessment, I develop resource response scenarios to incorporate irreducible uncertainty directly into the planning process and identify flexible and robust adaptation strategies for oak management. As land-cover and climate changes intensify, ecological planning practice must expand to include human-dominated landscapes, such as urbanizing regions, productively. In addition, management plans must be flexible and robust to future uncertainties. Understanding the ecological implications of these changes, and developing appropriate management and adaptation strategies, are essential tasks for ecological planners in the next century.
Thesis (Ph.D.)--University of Washington, 2013
Keywords: Biodiversity; Climate Change; Forest Regeneration; Quercus garryana; Seed Dispersal; Urbanization; Ecology; Urban planning; Conservation biology; urban planning